Surprise Box / Nor Ayuni Mohd Basri - Mohd Basri, Nor Ayuni (2021)
This report is about selling project which must be carried out individually so that the sales achievement of my business are reaches the target of RM250 for a month from 5 May until 5 June 2021. The name of my surprise box is ‘happiness by yun’ which is I do service in making a surprise box for my customer’s someone special. They can buy this surprise box for anyone you want such as for mother, father, wife and your best friend and what the most important is I give with special price that affordable to get. The business that I have choose is surprise box as my small business since a few months ago. It’s such a profitable business and easy to get sales since this pandemic Covid-19, most of people find an easy way to make a surprise delivery to someone special without get out from the house. So, people will find an easy way which is online surprise box just need to choose which set they want and pay. Then, the item will reach to someone they want to give. The reasons I still keep this business as my side income because easy to sell. Then I also love to do this business since this business just easy to do and I’m also happy when I surprised my customers. The main surprise box that I offered are cheap and affordable. Actually I was afraid to try expand my business because I need to spend more capital but finally my business survived. I got a lot of many returns and my sales increasingly known by people. Before this I was sale blouse and I was stopped selling that because of lack of knowledge. I was deceived by my supplier and most of item I got defect. Then I was down until I decide to wake up and start new business to get extra money. So, this report will show every process and activity about to get sales and how I run this business, in terms of project description before activity, project outcome after activity and my experience as a student to do a small business to achieve sales targets.